The haunting - Neeson, Liam.; Zeta-Jones, Catherine, 1969-; Wilson, Owen, 1968-; Taylor, Lili.; Bont, Jan de.; Jackson, Shirley, 1916-1965.; Self, David; Dreamworks Pictures; DreamWorks Home Entertainment (Firm) (Universal City, CA : DreamWorks Home Entertainment, 1999)
A professor lures three subjects to a mysterious mansion for an experiment which turns into a nightmare as the secrets of Hill House are revealed in this supernatural thriller.
Based on the novel The haunting of Hill House by Shirley Jackson.
"Special features: behind-the-scenes feature, 2 theatrical trailers, cast & filmmakers' bios, production notes."
Liam Neeson, Catherine Zeta-Jones, Owen Wilson, Lili Taylor.
Rated PG-13.
DVD, Dolby digital, 5.1 surround, 2.35:1 anamorphic widescreen, dual layer.
In English ; closed-captioned in English for the hearing impaired.
Keywords: Ghosts -- Drama; Feature films -- United States; Haunted house films; Films for the hearing impaired